Improving Children's Fine Motor Skills Through Cutting Activities with Banana Leaf Media in early childhood at PELITA HATI PAUD - Hakimah, Hakimah; Haryono , Mimpira; Sari , Rika Partika (CV. Generasi Insan Rafflesia, 2022)
The purpose of this study was to find out how to improve children's fine motor skills through cutting activities with banana leaf media in early childhood at PELITA HATI PAUD. Classroom Action Research (PTK) which is focused on classroom situations, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subjects in this study were children in group B (5-6 years), totaling 33 children in the village of Pematang Riding kec. Semidang Alas Maras district. As long as.. This Classroom Action Research uses the Jhon Elliot model where each cycle consists of four main activities, namely planning, implementing, observing, and reflecting which are carried out through two cycles, namely cycles I and II, each cycle consisting of one meeting. Data collection techniques using observation and documentation methods. Data analysis was carried out in a qualitative-quantitative descriptive manner with the emphasis being used to determine process improvements expressed in a predicate, while quantitative data analysis was used to determine yield improvements using percentages. The results of the research in Cycle I, can be seen to increase gradually. The improvements achieved in Cycle I have not yet reached the indicators of success that have been set, still with the criteria Developing According to Expectations. The results of the achievement percentage obtained in Cycle I could not reach a percentage of 64% (BSH criteria), so the research was continued in Cycle II. The results of the study in Cycle II, it can be seen that the child's ability to increase gradually the improvement achieved in Cycle II was able to achieve the predetermined success indicators, the results of the percentage of achievements obtained in Cycle II succeeded in achieving the Criteria of Very Good Development (BSB) with an increase in the percentage reaching 96 %.).